Community-Based Diabetes Mellitus Awareness and Blood Sugar Examination in Sukaraja Village, Medan City: English - Jody Yusuf (Asian Multidisciplinary Research Journal of Economy and Learning, 2024)
Diabetes Mellitus (DM) is one of the degenerative diseases whose prevalence continues to increase globally, including in Indonesia, due to modern lifestyle changes. The 2023 Independent Community Service Program (KKN) was held in Ward VIII, Sukaraja Village, Medan City, with the aim of increasing public knowledge and awareness about DM. This activity includes counseling on the definition, risk factors, symptoms, and prevention of DM, which is complemented by checking blood sugar levels for the community. It includes an educational approach with presentations and PowerPoint posters to keep participants interested, as well as two-way interaction through question and answer sessions. A total of 50 participants participated in this activity, with high enthusiasm and active participation during the discussion. The results of fasting blood sugar checks during KKN activities showed that 31 out of 50 participants (62%) had blood sugar levels above 126 mg/dL, which is included in the abnormal category. These findings indicate a high risk of diabetes in the local community. Education and intervention regarding a healthy lifestyle and regular check-ups are important steps to prevent and manage diabetes. The activity showed an increase in public understanding of DM, which was characterized by positive feedback during counseling and examination sessions. During the implementation of PowerPoint presentations on diabetes in KKN activities, some technical glitches may appear, such as hardware problems on laptops or projectors, PowerPoint files that do not open, or internet connection glitches if the material relies on online sources. Based on the evaluation, the program emphasizes the importance of continuous health education and cross-sector collaboration to increase public awareness of DM and other degenerative diseases.